Adaptive Energy Efficient Routing for Video Transmission in Wireless Multimedia Sensor Network Using Greedy Algorithm - V. Ranjith; C. Yaashuwanth; K. Prathibanandhi; T. Jayasankar (Tehnički Vjesnik, 2025)
Wireless sensor networks (WSNs) are distributed systems that present unique challenges compared to centralized networks, particularly in terms of energy consumption, service quality, and data delivery efficiency. Recent advancements in wireless multimedia sensor networks have facilitated applications such as video transmission via affordable mobile devices and cameras. However, these applications often suffer from issues related to end-to-end delay and bandwidth limitations. To address these challenges, this paper introduces a novel algorithm named the Predicted Transmission Count Delay Greedy Algorithm (PTC-DGA), designed to enhance the performance of WSNs under such constraints. Unlike the traditional Direct Diffusion-Based Algorithm (DDBA), which is data-centric and fails to adequately address delays, bandwidth limitations, throughput, and energy consumption, the PTC-DGA algorithm offers a robust solution by optimizing network quality, latency, and throughput. A key innovation of PTC-DGA is the integration of a Look-Ahead Algorithm to predict the cost of current sub-paths, thereby selecting the sub-path with the lowest predicted cost as the next cross point. This approach significantly improves the accuracy and robustness of sub-path selection. The effectiveness of the proposed PTC-DGA algorithm is validated through comparative analysis with the DDBA, using both tabulated results and graphical representations. The findings demonstrate that PTC-DGA not only addresses the limitations of DDBA but also provides substantial improvements in network performance metrics, including reduced delay, enhanced bandwidth utilization, and improved throughput.